An Analysis of the Efficacy of Sepia officinalis in the Management of Distress during Climacteric Years - Gupta, Jaya; Das, Biswo Ranjan (Indian Journal of Integrative Medicine, 2021)
Background- Climacteric is the phase in the ageing of women marking the transition from the reproductive phase to the non reproductive state. According to a survey, 44% of post menopausal women used hormonal replacement therapy (HRT). Aim: The present analysis is of the cases prescribed with Sepia officinalis to evaluate its efficacy in DDCY. Method- An open prospective observational study was undertaken by a research institute at six centers for a period of 4 years (including a follow up period of 1 year) as per the protocol. The cases where Sepia (n=53) was found indicated and prescribed were taken up for analysis. The data was analyzed statistically by using the “Wilcoxon sign rank test” on SPSS for the symptoms score and gynecological findings and “t test” for laboratory findings. Results- The mean symptom score at the base line was 13.68 (4.27) and at the end of treatment was 2.81 (2.63), which is statistically significant (P